Impact of different phased-array coils on the quality of prostate magnetic resonance images. (2021) - Stocker, Daniel; Manoliu, Andrei; Becker, Anton S.; Barth, Borna K.; Nanz, Daniel; Klarhöfer, Markus; Donati, Olivio F.
Highlights: Image quality is similar for different body phased-array receive coil setups. An 18-channel body phased-array receive coil setup achieved good image quality. 60-channel body phased-array receive coil setup slightly improves SNR in T2W images. Abstract: Purpose: To evaluate the influence of body phased-array (BPA) receive coil setups on signal-to-noise ratio (SNR) and image quality (IQ) in prostate MRI. Methods: This prospective study evaluated axial T2-weighted images (T2W-TSE) and DWI of the prostate in ten healthy volunteers with 18-channel (18CH), 30-channel and 60-channel (60CH) BPA receive coil setups. SNR and ADC values were assessed in the peripheral and transition zones (TZ). Two radiologists rated IQ features. Differences in qualitative and quantitative image features between BPA receive coil setups were compared. After correction for multiple comparisons, p-values <0.004 for quantitative and p-values <0.017 for qualitative image analysis were considered statistically significant. Results: Significantly higher SNR was found in T2W-TSE images in the TZ using 60CH BPA compared to 18CH BPA coil setups (15.20 ± 4.22 vs. 7.68 ± 2.37; p = 0.001). There were no significant differences between all other quantitative (T2W-TSE, p = 0.007−0.308; DWI, p = 0.024−0.574) and qualitative image features (T2W-TSE, p = 0.083–1.0; DWI, p = 0.046–1.0). Conclusion: 60CH BPA receive coil setup showed marginal SNR improvement in T2W-TSE images. Good IQ could be achieved with 18CH BPA coil setups.